2020
DOI: 10.1016/j.prrv.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Thromboinflammation in COVID-19 acute lung injury

Abstract: The reader will be able to appreciate: Thromboinflammation is a component of COVID-19 acute lung injury. Thromboinflammation has a multifactorial aetiology. There are multiple potential therapies for thromboinflammation, some already in clinical trials, that may benefit COVID-19 acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 42 publications
1
53
0
15
Order By: Relevance
“…A number of reports described the issue of pulmonary thrombosis in COVID-19 patients [ 7 , 8 ] and histologic analysis of pulmonary vessels in patients with COVID-19 showed widespread thrombosis with microangiopathy. Several pathological pathways are thought to be involved in microthrombi formation including endothelial damage, thrombin activation, platelet activation, neutrophil extracellular traps (NETs) formation, and contact pathway activation [ 9 ]. It is important to note the autopsy series of the some COVID-19 patients revealed diffusely edematous lung parenchyma and the presence of small and firm thrombi in sections of the peripheral lung, while pulmonary arteries at the hilum were free of thromboembolism and there were no signs of gross inflammation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports described the issue of pulmonary thrombosis in COVID-19 patients [ 7 , 8 ] and histologic analysis of pulmonary vessels in patients with COVID-19 showed widespread thrombosis with microangiopathy. Several pathological pathways are thought to be involved in microthrombi formation including endothelial damage, thrombin activation, platelet activation, neutrophil extracellular traps (NETs) formation, and contact pathway activation [ 9 ]. It is important to note the autopsy series of the some COVID-19 patients revealed diffusely edematous lung parenchyma and the presence of small and firm thrombi in sections of the peripheral lung, while pulmonary arteries at the hilum were free of thromboembolism and there were no signs of gross inflammation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important because more intense anticoagulation is associated with an increased risk of bleeding. In addition, the exuberant inflammatory response is known to play a role in the pathophysiology of acute respiratory distress syndrome (ARDS) [29] and especially that of COVID-19 [30,31]. Animal studies have shown that the inhibition of 3-hydroxy-3-methylglutarylcoenzyme A (HMG-CoA) reductase could modify several underlying mechanisms implicated in the development of ARDS [32].…”
Section: Statin Hypothesis Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%
“…In addition, hydroxyurea lowers VCAM‐1 and other soluble adhesion molecules 21 . Increased inflammatory cytokines, 22 a key role for monocytes and macrophages 23 and endothelialitis 24 have been implicated in COVID‐19 lung injury 25 . Hydroxyurea's therapeutic benefit could be related to the lower absolute monocyte counts, reduction of inflammatory cytokines, and decreased endothelial adhesive markers, but this needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%